Self-Dual Systems, their Symmetries and Reductions to the Bogoyavlensky Lattice - Fordy, A.P.; Xenitidis, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We recently introduced a class of ZN graded discrete Lax pairs and studied the associated discrete integrable systems (lattice equations). In particular, we introduced a subclass, which we called ''self-dual''. In this paper we discuss the continuous symmetries of these systems, their reductions and the relation of the latter to the Bogoyavlensky equation.